PEMANFAATAN INSTAGRAM SEBAGAI MEDIA PROMOSI PRODUK HAUS MELALUI AKUN @HAUS.INDONESIA - Asriyani Sagiyanto; Ayu Sulfiah (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2020)
At present the culinary business in Indonesia is increasingly in demand, from traditional food drinks to contemporary food and drinks. One of the culinary presentations of beverage products is Haus. Haus products are the Thai beverage with a combination of flavors. Haus also has its own way to promote its products, namely by utilizing social media. The social media that Haus uses to carry out promotions is Instagram. Instagram is an application that allows users to share photos / videos. The purpose of this study was to determine the use of selected intagrams as media promotions for thirsty products. The method used in this study uses a qualitative descriptive approach. With data collection techniques of observation, interviews, literature study and documentation. The results of this study indicate that thirst for using Instagram as a media promotion to introduce the latest products and variants accompanied by quizzes and give away in an interesting way along with posts about information about variants, the latest products, places, operating hours, stores. Haus utilizes Instagram social media that aims to introduce Haus products to be known in the community as the number one drink in Indonesia at an affordable price and can make Haus a national drink.